PERAN KONTEKSTUAL BADAN PENGAWAS PEMILIHAN UMUM PROVINSI LAMPUNG DALAM MENCEGAH POLITIK UANG PADA PELAKSANAAN PEMILIHAN UMUM - Fikri Isnaini Saputra; junaidi, Junaidi; Rafi Maulana Ramadhan (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2024)
Money politics as a form of election violation is the domain of Bawaslu as a supervisory institution to handle it in accordance with the provisions of the Election Law. The purpose of this research is to contribute ideas in creating honest and fair elections. Researchers used a qualitative method by analyzing the role of Bawaslu Lampung Province in preventing money politics. Researchers collected data using interview and documentation techniques. The results showed that Bawaslu Lampung Province had prevented money politics with the aim of supporting the realization of electoral justice. Prevention efforts include giving instructions in the institutional strengthening coordination meeting with Bawaslu Kab/Kota to form an anti-money politics patrol team, coordinating with KPU Kab/Kota, election participants, and ad-hoc supervisory committees. Other efforts include coordination with the Lampung Provincial KPU and cooperation to attract participatory supervisors. However, the efforts to prevent money politics are still not appropriate and effective with the conditions of the community and the geographical conditions of Lampung Province. For this reason, prevention efforts need to be carried out more humanistically and more massively. Efforts to prevent money politics are also still hindered by weak legal regulations that allow perpetrators to continue to carry out their actions. Thus, Bawaslu Lampung Province needs to voice the revision of weak articles in the Election Law so as to increase the effectiveness of prevention in the future.